(untitled) (Jurnal Peternakan Lingkungan Tropis, 2023)
This study aimed to determine the use of red dragon fruit peel extract (Hylocereus polyrhizus) as a natural dye in chicken sausages. The experimental design used was a completely randomized design (CRD). The factor in this study was the extraction time (hours) consisting of 4 treatments, namely 8 hours (P1), 9 hours (P2), 10 hours (P3), and 11 hours (P), and was repeated 4 times. Based on the results of this study, it is known that there is no significant effect on the extraction time of dragon fruit with the color, aroma, and taste of chicken sausage. Still, there is an effect on chicken sausage’s elasticity level, and the longer the extraction time, the lower the whiteness degree because the extraction time or immersion in ethanol is meager. Based on the results of the research that has been done, chicken meat sausage with red dragon fruit peel extract has a red color intensity value ranging from 4.78 to 6.82, with a red color intensity value of control sausage at 4.46. This proves that the addition of red dragon fruit peel extract increased the intensity of the red color of the chicken meat sausage produced.